Pengaruh Sistem Informasi Akuntansi, E-Commerce, Dan Self-Efficacy Terhadap Kinerja UMKM Di Kota Bengkulu - Violanda Rizqi; Iwin Arnova; Helmi Herawati (Jurnal Ilmiah Manajemen, Ekonomi dan Akuntansi, 2026)
The development of digital technology requires Micro, Small, and Medium Enterprises (MSMEs) to adapt in business management to improve performance and competitiveness. The implementation of Accounting Information Systems (AIS), the use of e-commerce, and self-efficacy of business actors are factors suspected to influence MSME performance. This study aims to analyze the influence of Accounting Information Systems, e-commerce, and self-efficacy on MSME performance in Bengkulu City, both partially and simultaneously. This study uses a quantitative approach with primary data obtained through the distribution of questionnaires to MSMEs in Bengkulu City. The analytical method used is multiple linear regression analysis with the help of the SPSS program 26. Hypothesis testing is carried out through the t-test to determine the partial effect, the F-test to determine the simultaneous effect, and the coefficient of determination (R²). The results of the study indicate that Accounting Information Systems and self-efficacy have a partial effect on the performance of MSMEs in Bengkulu City, while e-commerce has no partial effect on MSME performance. However, Accounting Information Systems, e-commerce, and self-efficacy simultaneously influence MSME performance. This indicates that improved MSME performance is more influenced by financial management skills and business actors' self-confidence than by individual e-commerce use. This research is expected to benefit MSMEs in improving business performance through strengthening financial management and developing self-efficacy, as well as serve as a consideration for local governments in designing targeted MSME development programs.